Association between early feeding of banana (Musa paradisiaca) and vomiting or abdominal distention in neonates - Hananto Wiryo; M Hakimi; A Samik Wahab; Pitono Soeparto (Indonesian Pediatric Society Publishing House, 2016)
Objective To assess the relationship between banana given as early solid food feeding and symptoms of intestinal obstruction (SIO) such as vomiting and abdominal distention among neonates. Methods A longitudinal cohort study was done in 1993 at a rural community of West Lombok District on Lombok Island, West Nusa Tenggara Province, Indonesia. There were 3420 neonates who were followed up by interviewing their mothers until 28 days after delivery. The main outcome measure was the occurrence of SIO. Results Compared to infants who were not given solid food, the relative risk (RR) of SIO for infants given food other than banana as early solid food feeding was 1.87 (95%CI 0.48;8.24), while for infants given banana only as early solid food feeding, the RR was 9.15 (95%CI 1.96;42.58). After the adjustments of birth weight, co- lostrum, and breast feeding, the odds ratio of SIO for infants given banana was 2.99 (95%CI 2.65;5.14). Conclusion Banana as early solid food for neonates feeding is an important risk factor for the occurrence of SIO